Major problems in the history of the vietnam war : documents and essays - McMahon, Robert ([S.l.] : Cengage Learning, 2007)
Designed to encourage critical thinking about history, the Major Problems in American History series introduces students to both primary sources and analytical essays on important topics in U.S. history. Major Problems in the History of the Vietnam War incorporates new research expands its coverage of the experiences of average soldiers.
Keywords: Vietnam War (1961-1975)